Pemanfaatan Ampas Tahu Dan Sampah Pasar Sebagai Pakan Larva BSF - Piyantina rukmini (Journal of Industrial Process and Chemical Engineering (JOICHE), 2021)
Dregs tofu and waste are organic materials that still contain a lot of good nutrition for larva feed.  The research aim to determine waste reductions by larva BSF.  This research uses a plastic box in which a mixture of tofu dregs, vegetable, and fruit are placed in certain composision.  No additional feed was added during this research.  The results shows that the mixture of dregs tofu and fruit (2 produce ECD= 10,2% and WRI = 3,1% higher than others containers/reactors.